Asbabul Wurud Based Hadith Learning Practice in Tahfidz Classroom: Praktik Pembelajaran Hadits Berbasis Asbabul Wurud di Kelas Tahfidz - zulfikar hidayat farizeni; Anita Puji Astutik (Academia Open, 2025)
General Background Learning strategies play a central role in shaping students’ understanding and religious character in Islamic education. Specific Background Hadith learning at the tahfidz program of PKBM Mutiara Shahabat integrates memorization activities, yet students often require contextual explanation to grasp meaning. Knowledge Gap Previous approaches have emphasized memorization, while the structured classroom use of the asbabul wurud method remains rarely documented in practice. Aims This study describes the implementation, strengths, and limitations of applying the asbabul wurud method in hadith science learning. Results Using a qualitative descriptive design with observation, interviews, and documentation, the findings show that the method is conducted through systematic planning, storytelling-based delivery of historical context, guided memorization, and continuous evaluation, enabling students to memorize faster, understand meanings, and practice hadith values in daily life. Novelty The study presents a classroom-based application of contextual hadith interpretation integrated into tahfidz routines. Implications The approach provides practical guidance for teachers to organize meaningful hadith instruction and supports collaboration between teachers, school leaders, and parents to sustain students’ religious learning outcomes. Keywords: Asbabul Wurud, Hadith Learning, Contextual Method, Tahfidz Education, Qualitative sSudy Key Findings Highlights: Structured storytelling supports quicker retention of texts Classroom routines connect historical context with daily behavior Multi level evaluation involves teachers families and supervisors